THE EFFECT OF USING MIND MAPPING ON STUDENTS’ ABILITY IN SUMMARIZING EXPLANATION TEXT - Syam, Nafa Anastasya; Korompot, Chairil Anwar; G, Hasriani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
The purpose of this research was to investigate the effect of using mind mapping on students’ ability in summarizing explanation texts. Conducted at SMPN 33 Makassar with 27 ninth-grade students, it employed a pre-experimental one group pre-test and post-test design. The findings show a significant improvement, with average scores increasing from 61.48 to 78.33. The paired samples t-test reveals a significant difference (t = 9.251, sig. = 0.000), and the N-Gain score of 0.44 indicates moderate improvement. The questionnaire analysis results also show positive student responses, with agreement rates ranging from 78.51% to 89.62%, indicating that students found mind mapping helpful in organizing ideas, identifying key points, and summarizing texts effectively. The study suggests that mind mapping is an effective method for enhancing summarizing skills in English learning. These findings imply that integrating visual learning strategies such as mind mapping into classroom instruction can support students’ comprehension and retention of textual content.Keywords: Mind Mapping, Summarizing Ability, Explanation Text, English Learning